LILIUM L. AYRIM NAVLARINI MANZARALILIK XUSUSIYATLARI VA XO‘JALIKDAGI AHAMIYATI BO‘YICHA INTRODUKSION BAHOLASH - Nasimova, Z.H. (SCIENCE and SOCIETY, 2024)
The main purpose of evaluating lilies is to use them in landscaping and grow them outdoors, as well as off-season plantings indoors. It fully reflects the decorative, economic and biological characteristics of varieties, taking into account their use, ensures the selection of the best promising varieties that meet the requirements of modern production.